2020
DOI: 10.1186/s12889-020-8260-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the impact of sleep duration on common mental disorders in school students

Abstract: Background Common mental disorders (CMD) in children and adolescents can be initial and non-specific manifestations of more serious mental diseases and often persist into adulthood. Therefore, early detection is important, as is the identification of the factors that impact development. Insufficient sleep represents one of the most common and potentially remediable risks to mental health in children and adolescents for whom chronic sleep loss has become normal. This study aims to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
4
8
0
7
Order By: Relevance
“…In the present study, we found that insufficient sleep duration occurred more often among females than males, with approximately 63.5% of males and 73.1% of females reported sleeping for less than 8 h on weeknights. The results obtained in this study are consistent with most other findings [ 46 48 ], although some studies have found no sex-related differences in sleep duration [ 49 , 50 ]. Differences across sex in this study could be due to females requiring more preparation time in the morning, and advanced onset of puberty in females may contribute to later bedtimes [ 48 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that insufficient sleep duration occurred more often among females than males, with approximately 63.5% of males and 73.1% of females reported sleeping for less than 8 h on weeknights. The results obtained in this study are consistent with most other findings [ 46 48 ], although some studies have found no sex-related differences in sleep duration [ 49 , 50 ]. Differences across sex in this study could be due to females requiring more preparation time in the morning, and advanced onset of puberty in females may contribute to later bedtimes [ 48 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found insu cient sleep duration would be more likely among females than males, approximately 63.5% of males and 73.1% females reported sleeping less than 8 h on weeknights. The result obtained in this study was consistent with most other ndings [46][47][48]. There were still some studies that found no sex-related difference in sleep duration [49,50].…”
Section: Discussionsupporting
confidence: 92%
“… 38 This delayed sleep onset can impair the transition to social hours, making it difficult for adolescents to remain awake in situations where they are expected to perform at their best, such as in school and during sports activities. Support for this idea comes from Agathao et al, 39 who recently documented a significant increase in common mental disorders score among Brazilian schoolchildren with short sleep hours. Therefore, further examination of these conditions is warranted, because everyday activities, school and extracurricular schedules, and a lack of frequent physical activity, as well as abnormal anthropometric parameters such as body mass index (BMI), and nocturnal waking and respiratory disorders, are predictors of pathologies consistent with daytime sleepiness.…”
Section: Discussionmentioning
confidence: 96%